2020
DOI: 10.1039/d0cp01667e
|View full text |Cite
|
Sign up to set email alerts
|

Detection of electric-quadrupole transitions in water vapour near 5.4 and 2.5 μm

Abstract: Electric-quadrupole transitions, presently detected by Fourier transform spectroscopy, contribute to the infrared absorption spectrum of water vapor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…largely below intensity values of the strongest electric-quadrupole lines (e.g. up to 10 -26 cm/molecule for water vapor [17]). The laboratory measurements of Refs [16,17] (in total, about twenty quadrupole lines near 5.4, 2.5 and 1.3 µm) have validated the ab initio intensities computed in Ref.…”
Section: H2o (Molecule 1)mentioning
confidence: 89%
See 3 more Smart Citations
“…largely below intensity values of the strongest electric-quadrupole lines (e.g. up to 10 -26 cm/molecule for water vapor [17]). The laboratory measurements of Refs [16,17] (in total, about twenty quadrupole lines near 5.4, 2.5 and 1.3 µm) have validated the ab initio intensities computed in Ref.…”
Section: H2o (Molecule 1)mentioning
confidence: 89%
“…Electric-quadrupole transitions do also exist, but they are typically a million times weaker than electric-dipole transitions, making their observation extremely challenging. The recent detection of weak quadrupole transitions in the spectrum of water vapor [16,17] has shown that in their present status the spectroscopic databases are not complete for polyatomic molecules. Actually, databases provide lists of electric-dipole transitions above an intensity cut-off (e.g.…”
Section: H2o (Molecule 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…The theory and programming work reported in Ref. [19] and in the present work have already been employed for generating hot molecular line lists for SiO 2 [45] and CO 2 [46] as well as to produce a quadrupole spectrum of H 2 O [47]. TROVE uses an automatic approach for constructing a symmetry-adapted basis set to be used in setting up a matrix representation of the molecular rotation-vibration Hamiltonian [48] In order to compute the vibrational energies for a linear molecule, we solve the Schrödinger equation for the HamiltonianĤ (0) vib,lin , which involves the bending and stretching motions and, as explained in Introduction, the rotational motion about the a axis.…”
Section: Introductionmentioning
confidence: 96%